The first two non‐Finnish HYLS1 variants: Expanding the phenotypic spectrum of hydrolethalus syndrome. Issue 4 (13th July 2021) - Ghesh, Leïla; Musquer, Marie Denis; Devisme, Louise; Stichelbout, Morgane; Boutaud, Lucile; Elkhartoufi, Nadia; Vaast, Pascal; Boute, Odile; Riteau, Anne‐Sophie; Le Vaillant, Claudine; Winer, Norbert; Joubert, Madeleine; et al.
Abstract: Hydrolethalus syndrome (HLS) is a rare lethal fetal malformation disorder related to ciliogenesis disruption. This condition is more frequent in Finland where a founder missense variant in the HYLS1 gene was identified. No other HYLS1 variant has hitherto been implicated in HLS. We report two unrelated French fetuses presenting with a phenotype of HLS with brain abnormalities, limbs malformations with pre and postaxial hexadactyly and abnormal genitalia. These two fetuses have compound heterozygous variants in HYLS 1. The first allele carries the same Finnish missense variant (NM_145014.2: c.632A > G, p.[Asp211Gly]) in both fetuses and the second allele carries a new missense variant (c.662G > C, p.[Arg221Pro]) in the first fetus, and a new nonsense variant (c.613C > T, p.[Arg205*]) in the second fetus. This is the first report of HYLS1 mutated cases outside Finland. Both cases presented here are consistent with HLS with additional malformations, allowing expansion of the phenotypic presentation previously described. Abstract :